Analysis of neuronal injury transcriptional response identifies CTCF and YY1 as co-operating factors regulating axon regeneration - Avraham, Oshri; Le, Jimmy; Leahy, Kathleen; Li, Tiandao; Zhao, Guoyan; Cavalli, Valeria (Frontiers in Molecular Neuroscience, 2022)
Injured sensory neurons activate a transcriptional program necessary for robust axon regeneration and eventual target reinnervation. Understanding the transcriptional regulators that govern this axon regenerative response may guide therapeutic strategies to promote axon regeneration in the injured nervous system. Here, we used cultured dorsal root ganglia neurons to identify pro-regenerative transcription factors. Using RNA sequencing, we first characterized this neuronal culture and determined that embryonic day 13.5 DRG (eDRG) neurons cultured for 7 days are similar to e15.5 DRG neurons in vivo and that all neuronal subtypes are represented. This eDRG neuronal culture does not contain other non-neuronal cell types. Next, we performed RNA sequencing at different time points after in vitro axotomy. Analysis of differentially expressed genes revealed upregulation of know regeneration associated transcription factors, including Jun Atf3 and Rest, paralleling the axon injury response in vivo. Analysis of transcription factor binding sites in differentially expressed genes revealed other known transcription factors promoting axon regeneration, such as Myc, Hif1, Ppar, Ascl1a, Srf and Ctcf, as well as other transcription factors not yet characterized in axon regeneration. We next tested if overexpression of novel candidate transcription factors alone or in combination promote axon regeneration in vitro. Our results demonstrate that co-expression of Ctcf with Yy1 or E2f2 enhances in vitro axon regeneration. Our analysis highlights that transcription factor interaction and chromatin architecture play an important role as a regulator of axon regeneration.